Front Cover: Chemical Stability of FeOOH at High Pressure and Temperature, and Oxygen Recycling in Early Earth History (Eur. J. Inorg. Chem. 30/2021). Issue 30 (21st July 2021) - Koemets, Egor; Fedotenko, Timofey; Khandarkhaeva, Saiana; Bykov, Maxim; Bykova, Elena; Thielmann, Marcel; Chariton, Stella; Aprilis, Georgios; Koemets, Iuliia; Glazyrin, Konstantin; Liermann, Hanns‐Peter; Hanfland, Michael; et al.
Abstract : The Front Cover shows a possible deep oxygen cycle in early Earth. FeOOH ("rust"), produced by anoxygenic photosynthesis and accumulated on the ocean floor, was transferred to the lower mantle by subducting slabs. At high pressures and temperatures, FeOOH decomposes into a mixture of complex iron oxides, water, and oxygen. Oxidizing fluids rising to the Earth′s surface could then possibly contribute to (or even be one of the main causes of) the Great Oxidation Event about 2.5 billion years ago. Image credits: Egor Koemets, Timofey Fedotenko, Leonid Dubrovinsky (Bayreuth University). More information can be found in the Full Paper by E. Koemets and co‐workers .